DIPG-10. TP53 PATHWAY ALTERATION IS DRIVING RADIORESISTANCE IN DIFFUSE INTRINSIC PONTINE GLIOMAS (DIPG). (23rd April 2019) - Werbrouck, Coralie; Silva-Evangelista, Clàudia; Lobón, Maria Jesus; Barret, Emilie; Teuff, Gwnenaël Le; Merlevede, Jane; Brusini, Romain; Kergrohen, Thomas; Bolle, Stéphanie; Beccaria, Kevin; Boddaert, Nathalie; Puget, Stéphanie; et al.
Abstract: Diffuse intrinsic pontine gliomas (DIPG) are the most severe pediatric brain tumours. Though accepted as the main therapeutic, radiotherapy is only transiently efficient and not even in every patient. We previously identified an heterogeneous response to radiotherapy at diagnosis depending on the type of histone H3 mutated (Castel et al., 2015). We aimed at defining possible molecular determinants of this response to radiotherapy. We assessed in vitro response to ionizing radiations in a collection of DIPG cellular models derived from treatment-naïve biopsies reflecting the variability encountered in patients and correlated it to their principal molecular alterations. The in vitro 50% lethal dose of these DIPG cellular models ranged from 0.5 to 7 Gy and were correlated to time to progression after radiotherapy in the corresponding patients. We uncovered TP53 mutation as the main driver of increased radioresistance. We validated this finding in 4 isogenic pairs of DIPG cells with TP53 WT and TP53 knock-down, confirming the pivotal role of TP53 inactivation in inducing DIPG radioresistance irrespective of the type of canonical or variant histone H3 mutated. Clinical and radiological response to radiotherapy and overall survival of an extended cohort of 73 DIPG was analysed according to their genotype and we demonstrated that mutated TP53 patients had a poor response to radiotherapy. Using a kinome-wide synthetic lethality RNAi screen, we further identified target genes that can sensitize TP53 MUT DIPG to ionizing radiations. CHK1 inhibition increases response to radiation specifically in TP53 MUT cells and could be considered as a new therapeutic approach in this setting. In all, TP53 alterations drive radioresistance in DIPG cells and TP53 mutational status is a biomarker to predict poor response to radiotherapy in patients. These findings will allow defining more tailored radiotherapy in DIPG and suggesting alternative treatment strategies to mitigate radioresistance with for example CHK1 inhibitors.